The ethics and legality of studying games with depressed participants - Hukkanen, Sonja (Bioethica, 2023)
This article examines gaming as a treatment for depression, focusing on the Finnish game Meliora and its research. Developed by Aalto University, Meliora aims to improve mental health of de-pressed individuals in conjunction with drugs for depression and therapy. Gaming as treatment is an innovation, and therefore, it is essential to research the legal and ethical dimensions that arise in these studies. The aim of the article is to indicate some specific issues that arise when conducting research on de-pressed people. It begins by presenting the relationship between gaming and mental health, discussing both the negative and positive effects of gaming in Chapter 2. Chapter 3 introduces Meliora and other innovations in the same industry along with a description of the research project. In Chapter 4, the focus is on bioethical and legal issues relating to research on depressed participants. The issues are discussed in light of the four biomedical principles: respect for autonomy, nonmaleficence, beneficence and justice. The chapter highlights concerns related to harm and risks, giving informed consent as a depressed or addicted individual, and the justification of excluding certain groups from the research. Finally, Chapter 5 provides a summary of the findings.